The BEE Model with Live Virtual Classroom to Enhancing Creative Works - N. Sitthimongkolchai; C. Viriyavejakul; S. Tuntiwongwanich (Emerging Science Journal, 2022)
Online learning is recognized as an effective teaching method and tool, widely integrated into different teaching and learning strategies to provide quality education at different levels. However, the field of design education does not have extensive research into online learning, delivery, and assessment. This study developed an online learning model for design disciplines to improve creative work effectively. This paper describes an empirical study to test the BEE model outcomes developed following previous research. This present study has focused on the intensity of the live virtual classroom in every step to compare differences in the scores of creative works. Therefore, the assumption was that Thai undergraduate design students who learned with the BEE model through live classroom learning (experimental group) would have at least one element of the creative work scores compared to the group learning through the traditional online teaching method (control group). Furthermore, we conducted a multistage randomized sample of 66 participants, divided into an experimental group of 33 participants and a control group of 33 subjects. To compare the scores of creative works, the test of creative works assessment rubric was used to collect the data. Then, they were analyzed using the MANOVA statistical test. The results found at least one element of them, and the average creative work scores of the experimental group showed that they were significantly higher than the control group (p<0.05). Doi: 10.28991/ESJ-2022-SIED-08 Full Text: PDF